2011
DOI: 10.1053/j.ajkd.2011.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Low 25-Hydroxyvitamin D Levels and Mortality in Non–Dialysis-Dependent CKD

Abstract: Background Low 25 hydroxyvitamin D (25[OH]D) levels are common among patients with non-dialysis-dependent chronic kidney disease (CKD). The associations between low 25(OH)D levels and mortality among non-dialysis dependent CKD patients are unclear. Study Design Retrospective cohort study. Setting & Participants Patients with stages 3–4 CKD (estimated glomerular filtration rate of 15–59 ml/min/1.73m2) (n = 12,673) who had 25(OH)D levels measured after the confirmation of CKD in Cleveland Clinic Health Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
37
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 26 publications
(35 reference statements)
4
37
0
1
Order By: Relevance
“…However, this association was abolished by the administration of active vitamin D sterols, suggesting that the use of such active sterols improves patient outcomes [34,35,36]. In our study, the patients had low 25-OH vitamin D levels, which were not elevated by the cinacalcet treatment but were decreased at the end of treatment.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, this association was abolished by the administration of active vitamin D sterols, suggesting that the use of such active sterols improves patient outcomes [34,35,36]. In our study, the patients had low 25-OH vitamin D levels, which were not elevated by the cinacalcet treatment but were decreased at the end of treatment.…”
Section: Discussionmentioning
confidence: 54%
“…Several studies had associated low 25-OH vitamin D levels with increased mortality and morbidity in non-dialysis-dependent patients with CKD [34,35] and ESRD [36]. However, this association was abolished by the administration of active vitamin D sterols, suggesting that the use of such active sterols improves patient outcomes [34,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm the data reported in the biggest retro spective observational study analyzing VD and mortality in CKD patients. Navaneethan et al [40] Taking all these data together, we agree with the Institute of Medicine recommendation to consider sufficient 25(OH)D levels of at least 20 ng/mL, given that serum 25(OH)D concentrations above 30 ng/ mL are not consistently associated with increased benefit [27,40] . In addition, most clinical trials have only confirmed the neutral effect of VD supplementation on hard outcomes [41] , whereas some controlled studies have shown positive results in spite of the mean VD concentration not reaching the optimal recommended levels of ≥ 30 ng/mL [16] .…”
supporting
confidence: 63%
“…3,15,16,27 Vitamin D deficiency is associated with cardiovascular disease, all-cause mortality, morbidity, poor clinical outcomes and rapid decline of eGFR in patients with CKD. 25,34,35 Our study has some limitations. First, 25(OH)D tended to decrease as PWV and CKD stage increased.…”
Section: Discussionmentioning
confidence: 94%